Information, Misinformation, and Disinformation About Covid-19: A Content Study of Closed-Cross Platform Messaging Using Whatsapp - Amit Verma, Maninder Kumar Singh, Dr. Aditi Pareek (International Journal of Advanced Science and Technology, 2020)
The whole world and India are a complete lockdown due to coronavirus, which we also have known as “Covid-19”. People are getting scared of print media because there is a fear among people that this virus spreads from the newspaper too. Subsequently, electronic media, it is social media, which is the most powerful medium of information in society. Nevertheless, it spreads more misinformation and is more frightening than the disease among people. In recent times, WhatsApp messenger has begun as an additional short message service in emerging nations. This one consists of a range of functions like the live location of a user, documents, audiovisual content, and text messages globally. Nowadays, whole things are going digitally from laypeople to an elite class is using WhatsApp so much that they do not use any other medium. Because it is an instant messaging service and we simply come to know about Information, Misinformation, and disinformation of the Coronavirus through WhatsApp. The purpose of doing this study is to content analysis of all the incoming and status messages on WhatsApp and turns it into junk middle fake content after the actuality of COVID-19, and the educated people of the society forward it and give rise to new violence in the community. The purpose of doing this study is to analyze the content of the incoming and status messages on WhatsApp and turn it into junk middle fake content after the actual.